Transcriptome profiling reveals insight into the cold response of perennial ryegrass genotypes with contrasting freezing tolerance - Akhil Reddy Pashapu; Gražina Statkevičiūtė; Ferenz Sustek-Sánchez; Mallikarjuna Rao Kovi; Odd Arne Rognli; Cecilia Sarmiento; Nils Rostoks; Kristina Jaškūnė (Plant Stress)
Low freezing tolerance threatens the survival and productivity of perennial ryegrass under northern climate. In this study, we aimed to identify transcriptional changes in plants subjected to low and freezing temperatures as well as to elucidate differences between tolerant and sensitive genotypes. Response to freezing stress was evaluated in a panel of 160 perennial ryegrass genotypes by measuring electrolyte leakage after exposure to -12 °C and -14 °C for 24 h. Two tolerant and two sensitive genotypes were selected for the transcriptome analysis. Crown tissue samples were collected at six treatments: before the start of cold acclimation (control point), at the start of acclimation, after one week of acclimation, after three weeks of acclimation, after freezing at -5 °C and freezing at -10 °C. A total of 11,125 differentially expressed genes (DEGs) were identified in the sensitive and 12,937 DEGs in the tolerant genotypes, when comparing the control vs. each of the acclimation and freezing treatments, as well as the end of acclimation vs. freezing treatments. Among the identified DEGs 3323 were unique to the sensitive genotypes, 5135 were unique to the tolerant genotypes and 7802 were shared. Genes upregulated during cold acclimation and freezing stress were linked to the MAPK signalling pathway, circadian rhythm, starch and sucrose metabolism, plant-pathogen interaction, carbon fixation, alpha-linoleic acid metabolism, carotenoid metabolism, glyoxylate and dicarboxylate metabolism pathways. Downregulated genes were linked to ATP-dependent chromatin remodelling, fatty acid elongation and DNA replication. The downregulation of fatty acid elongation and glutathione metabolism DEGs could indicate that the studied genotypes respond to cold stress in a novel or not yet well-characterized manner.